Pengaruh Current Ratio, Debt to Equity Ratio dan Kurs Nilai Tukar Rupiah terhadap Net Profit Margin pada PT Siantar Top Tbk Periode 2014-2023 - Kurniawan, Tommy; Octovian, Reza (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to determine the effect of Current Ratio, Debt to Equity Ratio, and Rupiah Exchange Rate on Net Profit Margin at PT Siantar Top Tbk for the period 2014-2023, both partially and simultaneously. The research method used is a descriptive method with a quantitative approach. The population in this study includes all financial report data (Annual Report) on PT Siantar Top Tbk available on the Indonesia Stock Exchange (IDX), while the sample used is the company's balance sheet and income statement for 10 years. The analysis techniques used in this study include descriptive analysis, classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation), multiple linear regression test, coefficient of determination (R²), and hypothesis testing consisting of partial testing (t-test) and simultaneous testing (f-test). The results of the data analysis were then processed using the Statistical Product and Service Solution (SPSS) version 25 program. The results of this study indicate that partially, the Current Ratio, Debt to Equity Ratio, and Rupiah Exchange Rate do not affect the Net Profit Margin. However, simultaneously, the Current Ratio, Debt to Equity Ratio, and Rupiah Exchange Rate have a positive and significant effect on the Net Profit Margin at PT Siantar Top Tbk.